Curcumin Attenuates Titanium Particle-Induced Inflammation by Regulating Macrophage Polarization In Vitro and In Vivo - Li, Bin; Hu, Yan; Zhao, Yaochao; Cheng, Mengqi; Qin, Hui; Cheng, Tao; Wang, Qiaojie; Peng, Xiaochun; Zhang, Xianlong (Frontiers in Immunology, 2017)
Periprosthetic inflammatory osteolysis and subsequent aseptic loosening are commonly observed in total joint arthroplasty. Other than revision surgery, few approved treatments are available for this complication. Wear particle-induced inflammation and macrophage polarization state play critical roles in periprosthetic osteolysis. We investigated the effects of curcumin, a polyphenol extracted from Curcuma longa, on titanium (Ti) particle-induced inflammation and macrophage polarization in vitro using the murine cell line RAW 264.7 and in vivo using a murine air pouch model. The expression of specific macrophage markers was qualitatively analyzed by immunofluorescence (iNOS and CD206) and quantitatively analyzed by flow cytometry (CCR7 and CD206), representing M1 and M2 macrophages, respectively. Our results show that curcumin induced a higher percentage of M2 macrophages together with a higher concentration of anti-inflammatory cytokine IL-10, and a lower percentage of M1 macrophages with a lower concentration of pro-inflammatory cytokines (TNF-α and IL-6). The genes encoding CD86 (M1) and CD163 (M2), two additional markers, were shifted by curcumin towards an M2 phenotype. C57BL/J6 mice were injected with air and Ti particles to establish an air pouch model. Curcumin reduced cell infiltration in the pouch membrane and decreased membrane thickness. The analysis of exudates obtained from pouches demonstrated that the effects of curcumin on macrophage polarization and cytokine production were similar to those observed in vitro. These results prove that curcumin suppresses Ti particle-induced inflammation by regulating macrophage polarization. Thus, curcumin could be developed as a new therapeutic candidate for the prevention and treatment of inflammatory osteolysis and aseptic loosening.